Infill Density Influence on Mechanical and Thermal Properties of Short Carbon Fiber-Reinforced Polyamide Composites Manufactured by FFF Process - Chicos, Lucia-Antoneta; Pop, Mihai Alin; Zaharia, Sebastian-Marian; Lancea, Camil; Buican, George Razvan; Pascariu, Ionut Stelian; Stamate, Valentin-Marian (MDPI AG, 2022)
In three-dimensional (3D) printing, one of the main parameters influencing the properties of 3D-printed materials is the infill density (ID). This paper presents the influence of ID on the microstructure, mechanical, and thermal properties of carbon fiber-reinforced composites, commercially available, manufactured by the Fused Filament Fabrication (FFF) process. The samples were manufactured using FFF by varying the infill density (25%, 50%, 75%, and 100%) and were subjected to tensile tests, three-point bending, and thermal analyses by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). It was shown that the samples with 100% ID had the highest values of both tensile, 90.8 MPa, and flexural strengths, 114 MPa, while those with 25% ID had the lowest values of 56.4 MPa and 62.2 MPa, respectively. For samples with infill densities of 25% and 50%, the differences between the maximum tensile and flexural strengths were small; therefore, if the operating conditions of the components allow, a 25% infill density could be used instead of 50%. After DSC analysis, it was found that the variation in the ID percentage determined the change in the glass transition temperature from 49.6 ◦C, for the samples with 25% ID, to 32.9 ◦C, for those with 100% ID. TGA results showed that the samples with IDs of 75% and 100% recorded lower temperatures of onset degradation (approximately 344.75 ◦C) than those with infill densities of 25% and 50% (348.5 ◦C, and 349.6 ◦C, respectively).
Keywords: fused filament fabrication; carbon fiber; polyamide; infill density; mechanical properties; thermal properties